Corrigendum: A Review of the Use of Linear Programming to Optimize Diets, Nutritiously, Economically and Environmentally (Front. Nutr., 2018 5 48 10.3389/Fnut.2018.00048) - Vasquez-Perez, O; Espinoza-Perez, A; Garcia-Leal, J (Frontiers Media S.A., 2022)
In the original article, there was a mistake in Table A1 as published. Reference [41] was duplicated twice in the table. Additionally, there were errors in the classification of the articles presented in Table A1. In the Acceptability column the original paper did not consider “portion size” as a constraint to diet optimization. In the revised Table A1 this has been added in the column Comments. The corrected Table A1 appears below. Full reference details for the references cited in the table can be found in the original article. In the original article there was also an error in reference [47]. The reference for [47] was incorrectly written as “Maillot M, Darmon N, Drewnowski A. Are he lowest-cost healthful food plans culturally and socially acceptable? Public Health Nutr. (2010) 13:1178–85. doi: 10.1017/S1368980009993028”. It should be “Maillot M, Darmon N, Drewnowski A. Are the lowest-cost healthful food plans culturally and socially acceptable? Public Health Nutr. (2010) 13:1178–85. doi: 10.1017/S1368980009993028”. In the original article, there also was an error in the section Results, Twelve Studies With Ecological Constraints, Paragraph 1. In the list “France, UK, and New Zealand”, France should not have been included and the reference [60] should not have been included. The updated paragraph appears below. Several studies—for instance in UK, andNew Zealand—have successfully applied LP to optimize diets (4, 19, 33, 38, 39, 44, 46, 47, 57). This section gives an overview of the 12 studies which have applied ecological constraints to 14 diets between 2000 and 2016 (13, 16–26). The studies are summarized in Table 1. The authors apologize for these errors and state that this does not change the scientific conclusions of the article in any way. The original article has been updated. © 2022 García-Leal, Espinoza Pérez, van Dooren and Vásquez.